Desempenho e saúde intestinal de leitões suplementados com DL ou L-metionina na fase de creche - Resende , Maíra (2016)
Methionine (Met) is an essential amino acid and usually the second or third limiting amino acid in conventional swine diets. It has a direct function in the synthesis of proteins, as well as in other biological functions, important for the performance and the health of the animals. The aim of this study was to investigate the performance and intestinal health of piglets supplemented with L-Methionine (L-Met) compared to DL-Methionine (DL-Met) in the nursery phase. Seventy-two pigs (barrows and gilts) of high genetic value, with initial BW of 6.30 ± 0.81 kg and 25 days of age (4 days post-weaning), were randomly in three treatments for 42 days: Basal diet deficient in Met (DB), DB + 0.06% of DL-Met and DB + 0.06% L-Met. DB meeting 66% of the requirement of methionine in pre-starter phase and 71% in starter phase, according NRC (2012). DLM diets and LM meeting 88% (pre-starter) and 95% (starter) of requirement. The animals were weighed individually and the supply of feed per pen measured daily, for to calculate the final BW, average daily gain (ADG), daily feed intake (ADFI) and feed conversion (FCR), considering the amounts of feed leftovers. Daily incidence of diarrhea was performed, calculated using the percentage of positive pens for diarrhea over the total period of observations carried out. At 42 days of trial, a barrow per pen was slaughtered and jejunum segments were collected for evaluation of intestinal morphology. At 43 days blood samples from the remaining barrow of the pen were collected for evaluation of plasma urea. From 0 to 28 d of evaluation, L-Met supplementation increased final BW and ADG when compared to DB. At the end of 42 days, animals supplemented with DL-Met had better ADG than animals receiving DB. In addition, there was a trend of improvement in the final BW (P = 0.065) and the animals of the DL-Met and L-Met groups had a BW 4.85 and 6.63% higher than the DB group, respectively. From 0 to 35 days, animals supplemented with L-Met had a lower incidence of diarrhea when compared to DB and DL-Met groups. In the total period, the L-Met group presented lower incidence than the DL-Met group. The results of PUN and villus height, crypt depth and villous:crypt jejunum were not different between treatments. In conclusion, LMet supplementation increases the average daily gain at 28 days of nursery phase and DL-Met at 42 days of nursery phase. L-Met supplementation reduces the incidence of diarrhea during the nursery phase.